Cardiac metastasis of triple-negative breast cancer mimicking myxoma: A case report. (November 2021) - Mallapasi, Muhammad Nuralim; Kusumanegara, Jayarasti; Kabo, Peter; Usman, Umar; Mulyono, Mario Tri; Faruk, Muhammad
Abstract: Introduction: Metastatic heart tumors are rare, occurring in 1.5–20% of cancer patient autopsies. Lymphoma, melanoma, leukemia, and carcinomas of the lung, esophagus, and breast are the most prevalent causes of these metastases, although they can originate from any malignant tumor. Here we report a case of triple-negative breast cancer with cardiac metastasis mimicking myxoma. Presentation of case: A 39-year-old woman presented at the emergency department with shortness of breath. Vital signs were hypotension and tachypnea. There were coarse crackles at the bases of both lungs. Electrocardiography results showed a normal sinus rhythm. Chest X-ray revealed cardiomegaly with signs of pulmonary edema. Echocardiography revealed a large left atrial (LA) mass protruding to the mitral valve and attached to the interatrial septum during diastole. The patient was diagnosed with cardiogenic shock, acute kidney injury, elevated liver enzymes, and an LA mass. Surgical excision through median sternotomy was planned. Intraoperatively, an LA mass was found. The histopathology evaluation showed an LA mass with invasive ductal carcinoma of metastatic breast tumors. Immunohistochemistry (IHC) confirmed the diagnosis of triple-negative breast cancer that had metastasized to the heart. Postoperative echocardiography confirmed complete excision of the tumor. Discussion: Breast cancer that has metastasized to the heart is uncommon. This patient was referred to the surgical oncology section for the treatment of triple-negative breast cancer with cardiac metastasis. Conclusion: A heart mass should be suspected of having metastasized if the patient has a history of malignancy, even if it occurred several years earlier. Highlights: Metastatic heart tumors are rare. Melanoma, and lung and breast carcinomas, are the most prevalent causes. In this case, cardiac metastasis of triple-negative breast cancer mimicked myxoma.